2019
DOI: 10.1177/1120672119845609
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between refractive state, corneal thickness, and keratometry in ametropic patients

Abstract: Purpose: To analyze the correlation between age, gender, refractive error, keratometry, and corneal thickness in a large group of subjects. Methods: This study is a retrospective analysis of patients who underwent refractive surgery between January 2000 and February 2015 at Care Vision Refractive Clinic, Tel Aviv, Israel. Patient demographics, subjective refraction, pachymetry, and average keratometry were collected. Results: Overall, 51,113 eyes of patients averaging 28.8 ± 9.3 years of which 53.9% were males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Rosenblatt et al proposed that an increase in magnitude of refractive error was correlated to lower keratometry values in hyperopia. (13) In addition, AlMahmoud et al reported that keratometry increased by 0.11 D for every diopter of decrease in refractive error across the entire range of refractive error. ( 14) Our case had more change in keratometry compared to previous study and possible changes in posterior corneal surface should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenblatt et al proposed that an increase in magnitude of refractive error was correlated to lower keratometry values in hyperopia. (13) In addition, AlMahmoud et al reported that keratometry increased by 0.11 D for every diopter of decrease in refractive error across the entire range of refractive error. ( 14) Our case had more change in keratometry compared to previous study and possible changes in posterior corneal surface should be considered.…”
Section: Discussionmentioning
confidence: 99%